Anthropometric analysis of lip-nose complex in Indian population - Khandekar, B; Srinivasan, S; Mokal, N; Thatte, M R (Indian Journal of Plastic Surgery, 2005)
One hundred normal individuals of different age groups from Mumbai (India) were included in this study. Various dimensions of lip-nose complex were measured. The results were compared with the available data for blacks, Caucasians and Chinese. In the population under study lip-nose complex measurements differ in all dimensions with blacks and Caucasians and show resemblance to the Chinese. The analysis of the data does not simply indicate the differences in the measurements but also points out change in growth patterns which will have a clinical significance.
Keywords: Anthropometry; lip-nose complex; Indian population